2020
DOI: 10.1016/j.amepre.2019.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Association of E-Cigarette Use With Respiratory Disease Among Adults: A Longitudinal Analysis

Abstract: Introduction: E-cigarettes deliver an aerosol of nicotine by heating a liquid and are promoted as an alternative to combustible tobacco. This study determines the longitudinal associations between e-cigarette use and respiratory disease controlling for combustible tobacco use. Methods:This was a longitudinal analysis of the adult Population Assessment of Tobacco and Health Waves 1, 2, and 3. Multivariable logistic regression was performed to determine the associations between e-cigarette use and respiratory di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
166
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(183 citation statements)
references
References 32 publications
10
166
2
5
Order By: Relevance
“…This is a prevailing argument that dual use of e -cigarettes and tobacco cigarettes does not reduce the respiratory risk from smoking, but may actually increase such risk. 48 Similar conclusions were presented in the NASEM report, particularly with regard to dual users. Although the report concluded that there is no evidence available that e -cigarettes cause respiratory diseases in humans, it also states that there is limited evidence of improved lung function and respiratory symptoms in adult asthma smokers who switch to e -cigarettes in full or in part (dual use).…”
Section: E -Cigarettes and The Risk Of Cardiovascular Diseasessupporting
confidence: 77%
“…This is a prevailing argument that dual use of e -cigarettes and tobacco cigarettes does not reduce the respiratory risk from smoking, but may actually increase such risk. 48 Similar conclusions were presented in the NASEM report, particularly with regard to dual users. Although the report concluded that there is no evidence available that e -cigarettes cause respiratory diseases in humans, it also states that there is limited evidence of improved lung function and respiratory symptoms in adult asthma smokers who switch to e -cigarettes in full or in part (dual use).…”
Section: E -Cigarettes and The Risk Of Cardiovascular Diseasessupporting
confidence: 77%
“…The outcome variable was any episode of wheezing in the past 12 months (yes or no) as reported on the wave 4 survey. For participants who completed the wave 3 survey (ie, participants whose data were used in this analysis), wheezing was assessed by asking, "Have you had wheezing or whistling in the chest in the past 12 Downloaded From: https://jamanetwork.com/ on 10/31/2020…”
Section: Outcome Variablementioning
confidence: 99%
“…6 In addition, there may be respiratory effects of ECs; one concern is that the use of ECs may be associated with risk of respiratory symptoms such as wheezing among youths. 7,8 Although the harmful respiratory effects of combustible tobacco use are well documented, [9][10][11][12] little is known about the respiratory effects of EC use. e-Cigarette aerosol contains several chemical constituents, such as diacetyl or benzaldehyde, that affect the respiratory system.…”
mentioning
confidence: 99%
“…Methodisch deutlich aussagekräftiger als Querschnittsuntersuchungen sind Kohortenstudien. Eine erste longitudinale Untersuchung beobachtete 26 646 US-Amerikaner, die bei der ersten Befragungswelle noch keine Atemwegserkrankungen hatten, über 2 Jahre [24]. Aktuelle E-Zigarettennutzer hatten verglichen mit Nicht-Konsumenten auch bei Kontrolle des ehemaligen und aktuellen Tabakkonsums ein adjustiertes Odds Ratio (aOR) von 1,29 (95 %-KI: 1,03 -1,61), im Beobachtungszeit eine Atemwegserkrankung zu entwickeln, bei Rauchern von Tabakzigaretten lag das adjustierte Chancenverhältnis bei 2,56 (95 %-KI: 1,92 bis 3,41).…”
Section: Vorhersage Des Ausstiegs Aus Dem Nikotinkonsumunclassified